The Effect Of Hand-Eye Coordination And Confidence On Badminton Smash Shot - Mangun, Fajar Arie; Subarkah, Ari (Gladi : Jurnal Ilmu Keolahragaan, 2024)
This study aims to determine the relationship between hand-eye coordination and confidence in badminton smash shots. The research methods used are an associative quantitative approach, a survey method with test and measurement techniques while the data analysis technique uses a path analysis approach. The study population is beginner athletes at the Gold Badminton Club and Sarwendah Badminton Club. The sampling technique used with total sampling is that the entire population is used as a sample. Based on the results of the data calculation, the value of Fcal = 4.612 was obtained and it was known that the significance value (Sig.) in the F test was 0.041. Because Sig. 0.041 < 0.05, it can be concluded that hand-eye coordination significantly affects the skill of the badminton game. For the calculation of confidence, the value of Fcal = 8.587 was obtained and it was known that the significance value (Sig.) in the F test was 0.007. Because Sig. 0.007 < 0.05, it can be concluded that Confidence (X2) has an effect on the Badminton Game smash hitting skill (Y) or means significant. So it can be concluded that based on the output table, the value of the coefficient or R square is 0.141. This value means that the influence of hand-eye coordination (X1) on the smash stroke skill of the badminton game (Y) is 14.1%, while the rest is influenced by other factors. Meanwhile, based on the output table, the value of the coefficient or R square is 0.235. This value means that the influence of Confidence (X2) on the smash hitting skill of the badminton game (Y) is 23.5% while the rest is influenced by other factors.